The Meta Analisis Pengembangan Instrumen Tes Keterampilan Proses Sains dalam Pembelajaran IPA (MAN Insan Cendekia Jambi, 2023)
The 21st century education requires that it produces quality human resources. The government is trying to answer the challenges of 21st century education through the development of the 2013 curri-culum. In science learning, discussing process skills Improve students' science learning process can be understood by updating. Real conditions in schools show that teachers have difficulty in talking. One solution is to develop an assessment instrument in the form of a test instrument for skills in learning science. This study tries to analyze the value of validity, different power, level of difficulty, and reliability of the process skills test instrument. The research method used is me-ta-analysis. The sample used was 7 articles consisting of 2 national articles. The research instrument used was an observation sheet complete with coding. The different power value is 0.31 in the sufficient category. The difficulty level value is 0.51, in the medium category. The reliability value is 0.64 in the high category. Thus, the science process skills test instrument can be continued to the trial stage.